Diseased-induced multifaceted variations in community assembly and functions of plant-associated microbiomes - Kuang, Lu; Li, Ting; Wang, Baozhan; Peng, Junwei; Li, Jiangang; Li, Pengfa; Jiang, Jiandong (Frontiers in Microbiology, 2023)
Plant-associated microorganisms are thought to be part of the so-called extended plant phenotypes with roles in affecting plant growth and health. Hence, understanding how plant-associated microorganisms respond to pathogen invasion is crucial to controlling plant diseases through manipulating plant microbiome. In this study, healthy and diseased (bacterial wilt disease, BWD) tomato (Solanum Lycopersicum L.) plants were harvested, and the variations in rhizosphere and root endosphere microbial communities were subsequently investigated using amplicon sequencing and shotgun metagenome sequencing. The results showed that BWD leaded to a significant increase in bacterial diversity in rhizosphere, but suppressed the bacterial diversity in root endosphere. The ecological null model indicated that BWD enhanced bacterial deterministic processes in both rhizosphere and root endosphere. Network analysis showed that microbial co-occurrence patterns were promoted by BWD. Moreover, higher universal ecological dynamics of microbial communities were observed in diseased rhizosphere. Metagenomic analysis revealed that more functional gene pathways were enriched in infected rhizosphere. More importantly, some plant-harmful pathways such as Quorum sensing were found to be significantly enriched, but some plant-beneficial functional gene pathways such as streptomycin biosynthesis were depleted by BWD. These findings broaden the understanding on the plant-microbiome interactions, and provide new clues to elucidate the mechanism underlying the interaction between plant microbiome and BWD occurrence.